Performance of calcium oxide as a heterogeneous catalyst in biodiesel production: A review - Boey, Peng-Lim; Maniam, Gaanty Pragas; Abd Hamid, Shafida (Elsevier, 2011)
The accelerating and frequently fluctuating price of conventional diesel, together with growing environ- mental concerns has sparked renewed attention on the search for an alternative fuel. The awareness of the toxic effects related to the tailpipe emissions of vehicles has driven many countries to look for a less-polluted transportation fuel. In this regard, biodiesel (alkyl esters) from vegetable oils or animal fats via transesterification is regarded as the most viable alternative as a green fuel for diesel engines. Trans- esterification is a catalyzed process and, traditionally, homogeneous catalysts are employed. However, this type of catalyst is not able to be reused and requires tedious washing and separating steps, hence, stimulating the conception of heterogeneous-catalyzed transesterification. Despite the success of various heterogeneous catalysts, many are not viable for wide industrial usage as most of the catalysts are expen- sive and need additional preparation effort. Among them, CaO seems to have a promising place and the increasing research on CaO is self-evidence of its capability in catalyzing the reaction. Therefore, in this paper, various issues regarding CaO-catalyzed transesterification are reviewed. The diverse performance of CaO in neat, loaded and mixed forms, as well as a support for other catalyst systems, CaO reaction mechanism, CaO tolerance to low to moderate oil qualities and reaction conditions, the conformance of CaO-catalyzed biodiesel to key specifications and the future outlook and the challenges of the catalyst are suitably addressed.